INVERSE NODAL PROBLEM FOR A p-LAPLACIAN STURM-LIOUVILLE EQUATION WITH POLYNOMIALLY BOUNDARY CONDITION - Koyunbakan, Hikmet; Gulsen, Tuba; Yilmaz, Emrah (Texas State Univ, 2018)
In this article, we extend solution of inverse nodal problem for one-dimensional p-Laplacian equation to the case when the boundary condition is polynomially eigenparameter. To find the spectral data as eigenvalues and nodal parameters, a Priifer substitution is used. Then, we give a reconstruction formula of the potential function by using nodal lengths. This method is similar to used in [24], and our results are more general.
Keywords: Inverse nodal problem; Priifer substitution; Sturm-Liouville equation